Sharpening Students’ Creative Thinking Skills Based on Spiritual Metaphysics by Using I'tikaf Muslim Method - Syarifuddin Syarifuddin (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This study aims to analyze the creative thinking skills of students based on spiritual metaphysics to determine the factors that influence the students' creative thinking skills using the I’tikaf Muslim method. Iktikaf worship means remaining silent and remaining in something. According to Hanafi scholars, iktikaf means staying silent in the mosque, which is usually used for congregational prayers, and according to Shafi'i scholars, iktikaf means remaining silent in the mosque by carrying out certain deeds with the intention of AllahThe research method is applied qualitatively with a case study method. The research sample is students of the Philosophy Science Study Program, totaling 20 students. This research was conducted on odd-semester Philosophy Study Program students in the 2022/2023 academic year. Data collection techniques using questionnaires and interviews with students. Data analysis techniques by reducing data, presenting data, and drawing conclusions. The analysis results were carried out to test the validity of the research data with data triangulation. The results showed a variation in the creative thinking skills of Philosophy students with a low category of 45%, medium 30%, and high 25%. The research conclusion shows that the factors influencing creative thinking skills are intelligence, knowledge, mindset, personality, motivation, and environment. The research implies that it can determine the appropriate Metaphysics learning model to improve the creative thinking competence of Philosophy students.